Cord blood-derived macrophage-lineage cells rapidly stimulate osteoblastic maturation in mesenchymal stem cells in a glycoprotein-130 dependent manner. - Tania J Fernandes; Jason M Hodge; Preetinder P Singh; Damien G Eeles; Fiona M Collier; Ian Holten; Peter R Ebeling; Geoffrey C Nicholson; Julian M W Quinn (PLoS ONE, 2013)
In bone, depletion of osteoclasts reduces bone formation in vivo, as does osteal macrophage depletion. How osteoclasts and macrophages promote the action of bone forming osteoblasts is, however, unclear. Since recruitment and differentiation of multi-potential stromal cells/mesenchymal stem cells (MSC) generates new active osteoblasts, we investigated whether human osteoclasts and macrophages (generated from cord blood-derived hematopoietic progenitors) induce osteoblastic maturation in adipose tissue-derived MSC. When treated with an osteogenic stimulus (ascorbate, dexamethasone and β-glycerophosphate) these MSC form matrix-mineralising, alkaline phosphatase-expressing osteoblastic cells. Cord blood-derived progenitors were treated with macrophage colony stimulating factor (M-CSF) to form immature proliferating macrophages, or with M-CSF plus receptor activator of NFκB ligand (RANKL) to form osteoclasts; culture medium was conditioned for 3 days by these cells to study their production of osteoblastic factors. Both osteoclast- and macrophage-conditioned medium (CM) greatly enhanced MSC osteoblastic differentiation in both the presence and absence of osteogenic medium, evident by increased alkaline phosphatase levels within 4 days and increased mineralisation within 14 days. These CM effects were completely ablated by antibodies blocking gp130 or oncostatin M (OSM), and OSM was detectable in both CM. Recombinant OSM very potently stimulated osteoblastic maturation of these MSC and enhanced bone morphogenetic protein-2 (BMP-2) actions on MSC. To determine the influence of macrophage activation on this OSM-dependent activity, CM was collected from macrophage populations treated with M-CSF plus IL-4 (to induce alternative activation) or with GM-CSF, IFNγ and LPS to cause classical activation. CM from IL-4 treated macrophages stimulated osteoblastic maturation in MSC, while CM from classically-activated macrophages did not. Thus, macrophage-lineage cells, including osteoclasts but not classically activated macrophages, can strongly drive MSC-osteoblastic commitment in OSM-dependent manner. This supports the notion that eliciting gp130-dependent signals in human MSC would be a useful approach to increase bone formation.